(untitled) (Docentes 2.0 Journal, 2026)
Interdisciplinary strategies constitute an essential pedagogical approach for fostering mathematical competencies in elementary school students, integrating disciplines to enhance learning and application in real-world contexts. The objective of this study was to apply and assess the effectiveness of interdisciplinary strategies for strengthening mathematical competencies among second-grade elementary school students. The research was conducted within the positivist paradigm, using the hypothetico-deductive method, with a quantitative approach and a quasi-experimental single-group design with pretest and posttest measurements. The study was explanatory and cross-sectional. The non-probability convenience sample consisted of 14 students. A performance test was administered, and the data were analyzed using descriptive statistics, the Shapiro-Wilk normality test (p > 0.05), a paired t-test (t(13) = 4.58, p = 0.00051), and Cohen’s d effect size (d = 1.29, 95% CI [0.51 – 2.07]). The results showed a significant increase in mean scores from 8.13 to 9.86 and a reduction in standard deviation from 1.54 to 0.36, indicating a substantial improvement in performance. In conclusion, this approach promotes the development of 21st-century skills, such as critical thinking and problem-solving, and serves as an effective pedagogical tool in elementary education.